Polynomial Equation Solver

Top
**Step 1 :**

**Step 2 :**

**Step 3 :**

**Step 4 :**

A polynomial is something which is expressed in the form of a(x^{n}) where n is non-negative integer.The variable 'a' is called as coefficient of x^{n} and n is the degree of the monomial.

The general representation of polynomial is given by

_{ }**Polynomial Equation Solver** solves the polynomial equation. The polynomials will be of the form: **A(x) = B(x)**

where**A(x)** and **B(x)** are the polynomials.

You can see a default equation given below. The calculator first factorize the equation with least common denominator to reduce the equation. Then, by solving the given equation, the calculator will find the value of the variable when you click on "Solve Equation".

The general representation of polynomial is given by

F(x) = a_{n}x^{n} + a_{n-1}x^{n-1} + a_{n-2}x^{n-2} + ........ + a_{1}x +a_{0}

_{}

where

You can see a default equation given below. The calculator first factorize the equation with least common denominator to reduce the equation. Then, by solving the given equation, the calculator will find the value of the variable when you click on "Solve Equation".

Reduce the given fraction by multiplying with least common denominator.

Simplify the given equation

Bring the terms of left side to the right side by changing the signs.

Lastly get the value of variable by solving the equation.

Solve:

$\frac{4x^{2} + 1}{3}$ = $\frac{3x^{2} + 5}{5}$

**Step 1 :**Multiply the whole polynomial equation by 15, we get

15 $\times$ $\frac{4x^{2} + 1}{3}$ = 15 $\times$ $\frac{3x^{2} + 5}{5}$

or

5 (4x

^{2}+ 1) = 3 (3x^{2}+ 5)**Step 2 :**20 x

^{2}+ 5 = 9x^{2}+ 15**Step 3 :**11 x

^{2}- 10 = 0

or

x

^{2}= $\frac{10}{11}$**Step 4 :**Solving the equation, we get

x = $\pm$ $\sqrt \frac{10}{11}$

**Answer :**There are two values:

x

_{1}= +$\sqrt \frac{10}{11}$ andx

_{2}= $\sqrt \frac{10}{11}$.Solve: 2x

^{2}- 3 = x**Step 1 :**Since the polynomial equation is not in fraction the equation remains as it is.

**Step 2 :**The given equation is also in simplified form so the equation remains the same.

**Step 3 :**2x

^{2}- 3 - x = 0**Step 4 :**solving the quadratic equation we get

2x

^{2}- 3x + 2x -3 = 0

x(2x - 3)+ 1(2x - 3) = 0

(x + 1)(2x - 3) = 0

**Answer :**There are again two values for x :

x

_{1}= -1 andx

_{2}= $\frac{3}{2}$.